Schizosaccharomyces pombe Grx4, Fep1, and Php4: In silico analysis and expression response to different iron concentrations - Ebrahim, Alia; Alfwuaires, Manal A.; Abukhalil, Mohammad H.; Alasmari, Fawaz; Ahmad, Fawad; Yao, Rui; Luo, Ying; Huang, Ying (Frontiers in Genetics, 2022)
Due to iron's essential role in cellular metabolism, most organisms must maintain their homeostasis. In this regard, the fission yeast Schizosaccharomyces pombe uses two transcription factors to regulate intracellular iron levels: fep1 under iron-rich conditions and php4 under iron-deficient conditions, which are controlled by grx4 gene. However, bioinformatics analysis to understand the role of these three genes in maintaining iron homeostasis in S. pombe is still lacking. Our study aimed to perform bioinformatics analysis on S. pombe (sp) and their sequence homologs in Aspergillus flavus (af), Saccharomyces cerevisiae (sc), and Homo sapiens (hs) to understand the role of Grx4, Fep1, and Php4 in maintaining iron homeostasis. The three genes' expression patterns were also examined at various iron concentrations. A multiple sequence alignment analysis of Grx4 revealed a conserved cysteine residue in each PF00085 domain. According to NCBI protein blast outcome, depending on query cover and identify percent, the hsGLRX3 is most similar to spGrx4. In addition, spFep1 is highly correlated with scDAL80, whereas scHAP4 is most similar to spFep1. We also found two highly conserved motifs in Fep1 that are significant for iron transport systems because they contain residues involved in iron homeostasis. The scHAP4 is most similar to spPhp4. Using STRING to analyze protein-protein interactions, we found that Grx4 interacts strongly with Php4 and Fep1. Furthermore, Grx4, Php4, and Fep1 interact with Php2, Php3, and Php5, indicating that the three proteins play cooperative roles in iron homeostasis. At the highest level of Fe, grx4 had the highest expression, followed by fep1, while php4 had the lowest expression; a contrast occurred at the lowest level of Fe, where grx4 expression remained constant. Our findings will enhance our knowledge of the structure and function of Grx4, Fep1, and Php4.